From Wine to Print: Reconstruction of Frankfurt Black Pigment and Intaglio Printing Ink. Issue 2 (2nd April 2020) - Kern, Marie; Stijnman, Ad; Müller, Jana; Wiegand, Yvonne; Brückle, Irene
ABSTRACT: 'Frankfurt Black' made of charred wine lees was often preferred above other charcoal pigments for intaglio printing in 17th to 19th centuries primary sources. As no samples of the dry pigment survive, it was experimentally recreated. Wine lees were charred according to historical instructions to determine appropriate conditions for dry pyrolysis (380°C, 300 min T). The pigment was ground with burnt oil varnishes prepared according to Abraham Bosse's 1649 manual on etching and engraving. Reconstructed Frankfurt Black was compared to hand-ground inks made with different plant black pigments and modern bone black printing ink. Impressions were made from an etched plate and compared for their colour, contrast, clarity of lines and details. Generally, Frankfurt Black ink displayed the properties described in historical sources: deep dark colour and a soft texture. The ink resembled modern inks in print. The study illustrates how the choice and manufacture of historical ink constituents can aﬀect the appearance of an intaglio print.